Sociedade, cultura e tratamento adequado: a gênese do conflito e a aplicação do método autocompositivo à luz da teoria do reconhecimento de Axel Honneth - Silva, Betânia Teodora Andrade da (2020)
The authors of classical liberal contractualism and German Idealism are credited with elaborating adverse philosophical currents capable of explaining the origin of society from the elements that form human nature and the motivational genesis of the conflict. The contemporary philosopher Axel Honneth, based on Hegel's reading proposes an analytical model of society that conflicts are no longer seen as an intrinsic characteristic of human beings to represent an anomaly stage in interactions, originated from one or repeated experiences of morally justified disrespect. It is from this reading that we take the conflict as a tool capable of expressing agendas regarding physical integrity and human dignity that, when taken to the sphere of law, can lead the individual to a positive self-understanding of himself, or, on the other hand, they can reaffirm the experience of disrespect that originated it and expand the negative self-understanding that prevents them from fully exercising their identity within the spaces in which they participate. With the election of Honnetian theoretical base, along with the empirical elements found in statistics and social indicators, this research aimed to correlate and understand the need for a philosophical and sociological reflection in the application of conflict treatment methods in the judicial sphere, especially in the self-composing, ostensibly fostered by laws of Brazil. The hypothesis studied is that when improperly applied or poorly conducted, the self-composing method of dialogical basis can lead to an exponential increase in frustrations and social illnesses that make effective pacification impossible, what, which, although initially providing the quantitative result desired by the National Policy for the Treatment of Conflicts, in the long term it will result in the return of these demands to the judiciary on a new guise, also frustrating the qualitative improvement in the exercise of the judicial function. In addition to offering a concise theoretical analysis for the defense of the proposed hypothesis and creating solid reflective bases for the continuation of research related to the theme we were able to verify that the application of self-compositive methods of dealing with judicial conflicts must consider the factors of social differentiation that unbalance and prevent an effectively fair dialogue within demands for recognition, that this practice must be exercised through an appropriate division between formal and material equality in the specific case; and that in the Democratic State of Law the Judiciary must actively contribute to realizing the social model of the constitution, which is done through a humanized treatment of the demands that allows the full recognition of all individuals.